Reducing Risk From First-of-kind In-situ Recoveryfor The Athabasca Basin - Chad Sorba; Dale Verran; David Bronkhorst; Jared Onyirimba; Jim Viellenave; Hal Demuth; Errol Lawrence (Canadian Institute of Mining, Metallurgy and Petroleum, 2020)
As outlined within the Denison Mines Corp’s (“Denison”) Pre-Feasibility Study ("PFS") completed in late 2018, additional work is required to increase confidence and reduce risk associated with the application of the In-Situ Recovery (“ISR”) mining method at the Phoenix deposit, located on the Wheeler River Uranium Project (“Wheeler River” or the “Project”) in northern Saskatchewan. The successful application of ISR in any geological environment largely hinges on three fundamental requirements, 1) permeability (of the deposit), 2) containment (of the mining solution) and 3) leachability (of the mineralization). Denison has designed several staged technical programs to progressively reduce risk associated with these requirements as the Company advances the Project toward a Feasibility Study (“FS”) and Environmental Impact Assessment (“EIA”). This paper will discuss the scope and results of certain technical programs being undertaken as the Company aims to develop the first ISR mining operation in the Athabasca Basin.